Forging the ‘New Opposition’: Resilience, Strategy, and Digital Contention in Post-Election Indonesian Civil Society - Alex Putra Pratama; Christian Napitupulu; Dais Susilo (HM Publisher, 2025)
In the wake of recent elections, Indonesia’s political landscape has seen a consolidation of power and the co-optation of formal opposition parties, creating a vacuum in democratic accountability. This study investigates the emergence of a ‘New Opposition’—a constellation of civil society coalitions that have assumed the role of a critical check on state power. We examine the strategies these coalitions employ, their internal dynamics, and the mechanisms underpinning their resilience in an increasingly restrictive political environment. This research employed a 12-month ethnographic mixed-methods approach from May 2024 to May 2025. We conducted 35 in-depth interviews with activists, lawyers, and academics; participant observation within a major civil society coalition in Jakarta; and three focus group discussions. This qualitative data was triangulated with quantitative analysis, including a Social Network Analysis (SNA) of 45 organizations to map collaborative structures and a survey (n=150) of activists to gauge perceived strategic effectiveness. Our findings reveal a strategic repertoire that blends legal-constitutional challenges, sophisticated public narrative framing, and digitally-enabled mobilization. SNA results demonstrate a significant increase in network density (from 0.21 to 0.45) and centralization following key political triggers, indicating a rapid consolidation of the coalition. Key ‘broker’ organizations, particularly in the legal aid and digital rights sectors, were crucial for connecting disparate clusters. While digital platforms were vital for mobilization, they also exposed activists to significant risks, including doxxing and state-sponsored cyber-attacks, creating a paradox of visibility and vulnerability. In conclusion, Indonesian civil society coalitions have effectively transformed into a resilient ‘New Opposition,’ characterized by adaptive strategies and a robust, networked structure. They function as a crucial bulwark for democratic norms, operating outside formal political structures. Their resilience is derived not from a single strategy but from the synergistic interplay of legal, narrative, and digital contention, sustained by a dense network of trust and shared purpose. This study underscores the critical role of networked civil society in upholding democratic accountability in hybrid regimes.